Post-marketing Study of Linagliptin: A Pilot Study - Gomes, Gabrielle Kéfrem Alves; Pereira, Mariana Linhares; Sanches, Cristina; Baldoni, André Oliveira (Frontiers in Pharmacology, 2019)
Introduction Linagliptin is a high-cost oral antidiabetic that has been widely used, and studies on its effectiveness and safety for the treatment of type 2 diabetes mellitus (DM2) in the real world is rare and necessary. Objective To analyze the values of glycated hemoglobin (HbA1c) and adverse events before and after the use of linagliptin in the post-marketing context of a pilot study. Methods This is a descriptive observational and exploratory study with a retrospective longitudinal approach, conducted between January 2014 and December 2016. All patients who participated in the study were over 18 years of age, with DM2, assisted by the Brazilian Public Health System (Sistema Único de Saúde – SUS) and had been indicated for use of linagliptin. The users were followed up and the variables of interest were collected from a computerized health information system (sistema informatizado de saúde – SIS) and patient records. For effectiveness analysis, HbA1c before (T0) and after (T1) the use of linagliptin was considered in patients registered as having collected linagliptin at the pharmacy for at least three consecutive months. For safety analysis, registered adverse events (AE) were verified in patients’ records. The sample was stratified according to the pharmacotherapeutic scheme of the users. To compare the means before (T0) and after (T1), a paired t-test (data with normal distribution) and Wilcoxon Signed Rank Sum test (non-normal distribution data) were performed. Results Considering the total population of the study, in a different pharmacotherapeutic regimen, a median reduction in HbA1c of -0.86% (p < 0.05) was observed. After stratification by pharmacotherapeutic regimen, the most significant reduction of HbA1c was -1.07% (p = 0.014) for the linagliptin group associated with insulins and oral antidiabetic agents (n = 13). On the other hand, patients taking linagliptin in monotherapy had the lowest HbA1c reduction, -0.48% (p > 0.05). AE occurred in 12 (36.4%) patients, and 16.7% were in monotherapy. Conclusion Linagliptin did not presented, in real world, the desired performance as showed in randomized premarketing clinical trials and it should be carefully evaluated in public health services.